Endothelial dysfunction and pregnancy-induced hypertension: a bibliometric analysis (2000–2024) - Ismawi, Hidayatul Radziah; Mohd Zainudin, Maizura; Zulkiflee, Khodijah (UniKL Royal College of Medicine Perak, 2025)
Background: This bibliometric analysis examines the evolving landscape of research on endothelial dysfunction and pregnancy-induced hypertension (PIH), focusing on trends, influential contributors, and key themes. Endothelial dysfunction in PIH significantly impacts maternal and foetal health, yet gaps remain in understanding its mechanisms and management. Objective: The study aims to provide a comprehensive overview of over two decades of publications on endothelial dysfunction and PIH to guide future research and clinical practice. Study design: Data were retrieved from Scopus, covering 397 publications over 25 years. Bibliometric measures, including citation metrics, co-authorship networks, and term co-occurrence maps, were analysed using the Scopus analytics tool and VOSviewer software. Key metrics included total citations, h-index, and term clustering, offering insights into publication trends, influential contributors, and thematic areas. Results: The analysis revealed an increasing trend in publications, being the United States and China as the most productive countries. Highly cited studies emphasised translational research linking clinical outcomes with mechanistic insights. Author keyword analysis highlighted research priorities including preeclampsia, hypertension, and oxidative stress. Co-occurrence maps revealed strategic and granular perspectives, highlighting angiogenesis, placental ischaemia, and long-term maternal health as critical themes. Limitations include reliance on Scopus data, which may exclude relevant studies indexed elsewhere. Conclusion: This study uniquely synthesises bibliometric insights to map the progression of endothelial dysfunction and PIH research. It highlights influential contributors, emerging trends, and key gaps, offering valuable guidance for researchers and policymakers. The findings highlight the importance of integrating mechanistic research with clinical applications to improve outcomes for hypertensive disorders in pregnancy.